2015
DOI: 10.1111/ejh.12578
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnostics of myeloproliferative neoplasms

Abstract: Since the discovery of the JAK2 V617F mutation in the majority of the myeloproliferative neoplasms (MPN) of polycythemia vera, essential thrombocythemia and primary myelofibrosis ten years ago, further MPN-specific mutational events, notably in JAK2 exon 12, MPL exon 10 and CALR exon 9 have been identified. These discoveries have been rapidly incorporated into evolving molecular diagnostic algorithms. Whilst many of these mutations appear to have prognostic implications, establishing MPN diagnosis is of immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 90 publications
(127 reference statements)
2
53
0
13
Order By: Relevance
“…TET2, DNMT3A and ASXL1. 10 In the current study, mutations were found in 35 additional genes (Figure 3 and Online Supplementary Table S3). All but one patient with MPL mutated ET had additional mutations, while in 39% of ET cases with JAK2 mutation (n=7) and 28% with CALR mutation (n=5) no additional mutations were found.…”
Section: 4mentioning
confidence: 53%
“…TET2, DNMT3A and ASXL1. 10 In the current study, mutations were found in 35 additional genes (Figure 3 and Online Supplementary Table S3). All but one patient with MPL mutated ET had additional mutations, while in 39% of ET cases with JAK2 mutation (n=7) and 28% with CALR mutation (n=5) no additional mutations were found.…”
Section: 4mentioning
confidence: 53%
“…Indeed, apart from JAK2 V617F , MPL , and CALR mutations, several other gene mutations have been described: TET2 (in 5% of cases), DNMT3A (in 1–5%), and ASXL1 (in 2–5%) [16]. Thirty-five other gene mutations have been reported [7].…”
Section: Discussionmentioning
confidence: 99%
“…A Philadelphia-negatív klasszikus myeloproliferativ neoplasiák (MPN) köré-be tartozik az essentialis thrombocythaemiával (ET) és a primer myelofibrosissal (PMF) együtt. A kórkép kialakulására jellemző a JAK-STAT jelátviteli útvonal folyamatos, konstitucionális aktivációja, amely a myeloproliferatióhoz vezet [1,2].…”
unclassified